Densidad y estructura poblacional del cangrejo azul Cardisoma guanhumi (Latreille, 1828) (Decápoda: Gecarcinidae) en dos bosques de manglar de San Bernardo del Viento, Córdoba, Colombia (2022)
The objective of this research was to evaluate the density and population structure of the blue crab, Cardisoma guanhumi, in two mangrove forests in the region of San Bernardo del Viento, Córdoba, Colombia. The blue crab is a species categorized as vulnerable according to the Red Book of Marine Invertebrates of Colombia, due to the loss of its habitat and indiscriminate capture. In turn, it plays a key role within the mangrove ecosystems and is of great economic, cultural and social importance in the Darién areas of Córdoba. However, the status of its population was unknown in the area. Therefore, two sites were chosen; town The Salvador and Punta Manzanillo, during six samplings between the months of December 2020 and July 2021, density was estimated using two methods: direct and indirect. In turn, the individuals were captured using three methods: braceado, traps and manual, with which it was recorded; sex, color pattern and morphometric characteristics. On the other hand, an ethnoecological approach was taken, through surveys that helped identify social aspects of the blue crab in the inhabitants of Paso Nuevo. A total of 287 individuals of C. guanhumi were captured and 408 burrows were sampled. Based on the t-Student test, no statistically significant differences were found in the densities at the two selected points. Of the total individuals captured, 66.9% were adult males, 33.0% adult females, 22.6% pre-adults, 3.5% juveniles and 20% ovate females correspond to V. El Salvador. In P. Manzanillo, 76.7% are adult males, 23.2% adult females, 14.5% preadults, 1.61% juveniles, and 12.9% ovate females. It was determined that adult males reach larger sizes and weights, obtaining slightly higher values in P. Manzanillo. The overall sex ratio was 1M:1F, but changed in P. Manzanillo to 0.5:1 (M: F), biased towards males. Frequencies in males tend to have greater variation in size, being located in all the intervals found. On the other hand, most of the respondents distinguish the sex by observing the width of their abdomen, they indicate that the blue crab has breeding seasons that coincide with the rainy season and that is when they usually see more crabs, but in dry weather, they hide in their burrows to protect themselves when they are in moult. The results presented here contribute to the study of the species and understanding of its biology in this region of Cordoba, in order to initiate processes that lead to its regulation and measures for the sustainable management of this resource. Keywords: Density, blue crab, morphometric characteristics, ethnoecological, sustainable.